S26 Feasibility and patient tolerability of transcutaneous electrical stimulation in obstructive sleep apnoea. (15th November 2016) - Reed, KI; Pengo, MF; Xiao, S; Ratneswaran, C; Shah, N; Chen, T; Douiri, A; Hart, N; Luo, Y; Rafferty, GF; Rossi, GP; Williams, A; et al.
Abstract : Introduction: Transcutaneous electrical stimulation (TES) provides neuromuscular tone to the pharyngeal dilator muscles of the upper airway (UA) while asleep, but feasibility of this method to treat obstructive sleep apnoea (OSA) throughout the whole night has not been tested. Patients and methods: We conducted a phase two double-blind, sham-controlled, randomised controlled trial using TES of the UA muscles in 36 patients with confirmed OSA to assess patients' device acceptance and the side effect profile. Patients were studied using polysomnography during randomly assigned nights of sham-stimulation and active treatment following titration of the current while awake. Assessment of patients' device acceptance and experience of side effects was measured using a visual analogue scale (0–10 points) where high scores indicated better outcomes. Results: We included 36 patients (age mean 50.8 (SD 11.2) years, male/female 30/6, body mass index median 29.6 (IQR 26.9–34.9) kg/m 2, Epworth Sleepiness Scale 10.5 (4.6) points, oxygen desaturation index median 25.7 (16.0–49.1)/hour, apnoea-hypopnoea index median 28.1 (19.0–57.0)/hour). None of the patients reported skin discomfort, unpleasant tongue sensations or morning headache. There was no difference in patients' perceived sleep quality. There was a 59% reduction in mouth dryness after active treatment compared to sham-stimulation. There were no severe adverse events (Table). Conclusion: TES of the UA dilator muscles in OSA can be delivered throughout the night with few side effects and does not lead to arousal from sleep, if appropriately titrated.